2021
DOI: 10.1177/11297298211011875
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical sources of neointimal cells in the arteriovenous fistula

Abstract: Neointimal cells are an elusive population with ambiguous origins, functions, and states of differentiation. Expansion of the venous intima in arteriovenous fistula (AVF) is one of the most prominent remodeling processes in the wall after access creation. However, most of the current knowledge about neointimal cells in AVFs comes from extrapolations from the arterial neointima in non-AVF systems. Understanding the origin of neointimal cells in fistulas may have important implications for the design and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…The artery injury model is induced by completely removing the endothelial layer and causing a distending mural injury in rat/mice with normal kidney function (48). In patients with kidney failure, uremic milieu contributes to a multitude of vascular diseases including venous intimal hyperplasia even prior to hemodialysis access surgery (7,49,50). Our studies showed that expression level of endothelial JMJD3 in vessel was significantly decreased in the context of chronic renal failure.…”
Section: Western Blot Analyses Revealed That the Expression Ofmentioning
confidence: 63%
See 1 more Smart Citation
“…The artery injury model is induced by completely removing the endothelial layer and causing a distending mural injury in rat/mice with normal kidney function (48). In patients with kidney failure, uremic milieu contributes to a multitude of vascular diseases including venous intimal hyperplasia even prior to hemodialysis access surgery (7,49,50). Our studies showed that expression level of endothelial JMJD3 in vessel was significantly decreased in the context of chronic renal failure.…”
Section: Western Blot Analyses Revealed That the Expression Ofmentioning
confidence: 63%
“…Neointimal hyperplasia (NIH) is present in most native veins and AVFs, which is prominent in many patients with kidney failure (7). After AVF creation, expansion of neointima may aggravate inward remodeling leading to the development of stenosis and access failure.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn may lead to neointimal hyperplasia and venous stenosis. 24,25 Muscle contractions occurring during upper limb exercise training is the major stimulus to increase blood flow and WSS. 26 It has been found to be associated with endothelium-dependent vasodilation, probably through an increase in nitric oxide (NO) bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis can be located in any part of the vascular access, but it is most common at the venous end and the anastomosis of the internal fistula. The main pathological basis is venous intima hyperplasia (Vazquez-Padron et al 2021), which is composed of endothelial cells, vascular smooth muscle cells (SMCs), macrophages, fibroblasts, myofibroblasts and a large amount of extracellular matrix (ECM), while CHI3L1 is expressed by different types of cells including SMCs, macrophages, neutrophils (Yeo et al 2019). Thus, it is supposed that CHI3L1 might also have an impact on the failure of AVF in ESRD patients, apart from the molecular mechanisms already demonstrated by several studies, such as inflammation, uremia, hypoxia, and sheer stress, which are responsible for the AVF failure (Brahmbhatt et al 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%